Merchants of the right : gun sellers and the crisis of American democracy - Carlson, Jennifer (Princeton, New Jersey : Princeton University Press, 2023)
"Gun sales have not just surged in the past two years-they have skyrocketed, breaking all-time records from March to July 2020. In this book, Jennifer Carlson examines the three dire crises in the United States in 2020-the pandemic, police murders and subsequent uprisings for racial justice, and the 2020 elections-to examine how Americans have turned to a well-worn tool of security in American life: the gun. While the notion that Americans would turn to guns for safety and security is hardly new, the utility of guns amidst the collective crises of 2020 is not so straight-forward. Carlson documents how people positioned at the frontlines of gun culture and conservative politics-namely, gun sellers-navigate the mismatch between guns as an esteemed tool of safety and security in the US context and the real-life crises that guns are deemed capable of solving, not least because many Americans believe they have no other option. Drawing on in-depth interviews with over 50 gun sellers across the United States and pro-gun media, as well as historical and legal accounts, Carlson explores the politics of gun rights in 2020 as a window into the broader challenges currently faced by American democracy. She begins with the National Rifle Association's transformation into a political organization in the second half of the 20th century and identifies three tools that were essential to that transformation: armed individualism, conspiracism, and partisanship. Focusing on each tool in subsequent chapters, she argues that gun owners, gun sellers, and gun rights advocates have used these tools to not just defend gun rights but also to understand and engage the political tensions they confront in their everyday lives. In doing so, she illuminates the underlying processes by which conservative Americans have deepened contempt for liberal democracy, and with what consequences"--
"An eye-opening portrait of the gun sellers who navigated the social turmoil leading up to the January 6 Capitol attackGun sellers sell more than just guns. They also sell politics. Merchants of the Right sheds light on the unparalleled surge in gun purchasing during one of the most dire moments in American history, revealing how conservative political culture was galvanized amid a once-in-a-century pandemic, racial unrest, and a U.S. presidential election that rocked the foundations of American democracy.Drawing on a wealth of in-depth interviews with gun sellers across the United States, Jennifer Carlson takes readers to the front lines of the culture war over gun rights. Even though the majority of gun owners are conservative, new gun buyers are more likely to be liberal than existing gun owners. This posed a dilemma to gun sellers in the run-up to the 2020 presidential election: embrace these liberal customers as part of a new, perhaps postpartisan chapter in the American gun saga or double down on gun politics as conservative terrain. Carlson describes how gun sellers mobilized mainstays of modern conservative culture-armed individualism, conspiracism, and partisanship-as they navigated the uncertainty and chaos unfolding around them, asserting gun politics as conservative politics and reworking and even rejecting liberal democracy in the process.Merchants of the Right offers crucial lessons about the dilemmas confronting us today, arguing that we must reckon with the everyday politics that divide us if we ever hope to restore American democracy to health"--
Cover -- Contents -- Preface -- Introduction: Democracy Disarmed -- Armed Individualism -- Chapter 1: Viral Gun Rights -- Conspiracism -- Chapter 2: Conspiracism for the People -- Partisanship -- Chapter 3: America Unmasked -- Democracy -- Chapter 4: At the Edge of Democracy -- Conclusion: The Democracy We Deserve -- Epilogue -- Acknowledgments -- Reflections on Methodology -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 27, 2023).
JSTOR
Keywords: Firearms ownership -- Political aspects -- United States; Democracy -- United States; Conservatism -- United States; Right-wing extremists -- United States; Polarization (Social sciences) -- United States; Armes à feu -- Possession -- Aspect politique -- États-Unis.; Conservatisme -- États-Unis.; Extrémistes de droite -- États-Unis.; Polarisation collective -- États-Unis.; SOCIAL SCIENCE / Violence in Society; SOCIAL SCIENCE / Sociology / General; Conservatism; Democracy; Polarization (Social sciences); Right-wing extremists; United States; Electronic books